Analysis of Opportunities and Challenges in the Implementation of Sharia Regional Regulations in the Era of Regional Autonomy in Luwu Regency - Muhammad Akbar (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to find out the opportunities for forming sharia regional regulations and the challenges faced in forming sharia regional regulations in Luwu Regency. Qualitative descriptive research, because it intends to find out the opportunities and challenges of implementing Sharia regulations in Luwu Regency. So that the Sharia regional regulations are seen as a solution to the problems of local government in general and Luwu Regency in particular. Data collection was carried out by observing, interviewing related parties, and collecting data from documentation deemed appropriate to the theme of this research. The results of the study show that: 1. Sharia Regional Regulations are statutory regulations established by the Regional People's Legislative Council with the joint approval of the Regional Head (Governor or Regent).